MANAJEMEN PEMELIHARAAN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMAN 1 PURWAKARTA - Rhamdani, Nuron; Yoseptry, Ricky; Alam, Rudi; Trianugrahwati, Desemberi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
This research aims to get an overview of the maintenance management of facilities and infrastructure in improving the quality of learning. This research was carried out at SMA Negeri 1 Purwakarta. This research refers to the management theory of G.R. Terry to see the implementation of facilities and infrastructure maintenance management at SMA Negeri 1 Purwakarta. This research uses a qualitative approach with descriptive methods because researchers want to get an in-depth picture of problems in the field. Data collection was carried out by observation, interviews, and documentation studies. The results of this research show that: 1). Planning for maintenance of facilities and infrastructure is programmed globally, according to repair needs, the budget plan is detailed and then proposed through RKAS. 2). Organizing the maintenance of facilities and infrastructure is carried out by all school personnel, both teachers and students. 3). Implementation of maintenance of facilities and infrastructure includes two activities, namely light repairs and heavy repairs. 4). Supervision of maintenance of facilities and infrastructure is carried out by reporting activities by teachers or deputy heads of facilities and infrastructure and evaluated at the end-of-year meeting.